A DESCRIPTIVE STUDY OF SUBJECT INDEXING AND ABSTRACTING IN INTERNATIONAL INDEX TO MUSIC PERIODICALS, RILM ABSTRACTS OF MUSIC LITERATURE, AND THE MUSIC INDEX ONLINE. - Jenkins, Martin D. (Notes, 2001)
Describes three major online databases dedicated to the indexing of the literature of music, The Music Index, RILM Abstracts of Music Literature and International Index to Music Periodicals. Averages for each database in each journal group; Averages for English and non-English articles.